DESIGUALDADES SOCIAIS, QUESTÃO SOCIAL E POLÍTICAS PÚBLICAS - Simone de Jesus Guimarães (Universidade Federal do Maranhão, 2018)
Brazil is a deeply unequal country. Wealth and socially produced goods are concentrated in the hands of few. Social issues, synthesis of all the inequalities that affect the country, deepen with the rising of Michel Temer to the Presidency (2016), through a parliamentary coup. Public policies State’s responses to the social issues are being weakened and modified by reforms that affect workers’ rights, guaranteed by the Constitution and other regulations. The objective of this paper is to discuss the Brazilian reality in relation to inequality, social issues and public policies.